SUBSTITUTION OF UREA FERTILIZER WITH COW MANURE ON THE GROWTH AND YIELD OF KATE ELEPHANT GRASS (Pennisetum purpureum cv. Mott) - I M., Aginandita; Kusumawati, N. N. C.; Wirawan, I W. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the substitution of urea fertilizer with cow manure on the growth and yield of kate elephant grass ( Pennisetum purpureum cv. Mott). This research was conducted at the Greenhouse of Sading Village, Mengwi District, Badung Regency. This study lasted for 8 weeks, using a completely randomized design (CRD) with 5 dosage of treatment fertilizer and 5 replications so that there were 25 experimental units. The treatments given were A = 200 kg urea ha -1 ; B = 150 kg urea ha -1 + 5 tons of cow manure ha -1 ; C = 100 kg of urea ha -1 + 10 tons of cow manure ha -1 ; D = 50 kg urea ha -1 + 15 tons of cow manure ha -1 ; E = 20 tons of cow manure ha -1 . The variables observed in this study were growth variables, yield variables, and growth characteristics variables. The results showed that substitution of urea with cow manure could increase the growth and yield of kate elephant grass ( Pennisetum purpureum cv. Mott). The dosage of cow manure fertilizer of 20 tons ha -1 gave the best results in increasing the growth and yield of kate elephant grass. It can be concluded that the use of cow manure at a dosage of 20 tons ha -1 gave the best growth and yield of kate elephant grass ( Pennisetum purpureum cv. Mott). Keywords : cow manure, substitution urea, Pennisetum purpureum cv. Mott